Impact of Louisiana's HPV Vaccine Awareness Policy on HPV Vaccination Among 13- to 17-Year-Old Females. (August 2017) - Pierre-Victor, Dudith; Trepka, Mary Jo; Page, Timothy F.; Li, Tan; Stephens, Dionne P.; Madhivanan, Purnima
The Advisory Committee on Immunization Practices recommends routine human papillomavirus (HPV) immunization for 11- to 12-year-old adolescents. In 2008, Louisiana required the school boards to distribute HPV vaccine information to parents or guardian of students in Grades 6 to 12. This article investigates the impact of this policy on HPV vaccination among 13- to 17-year-old female adolescents using National Immunization Survey-Teen (NIS-Teen) data. Drawing on the data from the 2008 to 2012 NIS-Teen, we compared the difference in proportions of females who have been vaccinated before and after the policy. Using difference-indifference estimation, we explored the change in vaccination rates before and after the policy implementation in Louisiana compared with Alabama and Mississippi, two states that did not have such a policy in place. The difference-in-differences estimates for HPV vaccination were not significant. Physician recommendation for HPV vaccination was significantly associated with vaccination among females in Louisiana and Alabama (adjusted odds ratio [aOR] = 7.74; 95% confidence interval [CI; 5.22, 11.5]), and for those in Louisiana and Mississippi (aOR = 7.05; 95% CI [4.6, 10.5]). Compared to the proportion of female adolescents who had received physician recommendation in Alabama or Mississippi, the proportion in Louisiana did not increase significantly in the postpolicy period. HPV vaccination rates did not increase significantly in Louisiana compared to Alabama or Mississippi following the implementation of the policy. Despite Louisiana's policy, physician recommendation remains the key determinant of HPV vaccination. HPV vaccine awareness does not necessarily result in HPV vaccination.